2022
DOI: 10.37201/req/008.2022
|View full text |Cite
|
Sign up to set email alerts
|

High incidence of COVID-19 at nursing homes in Madrid, Spain, despite preventive measures

Abstract: Objective. To assess the impact of COVID-19 at nine nursing homes in Madrid, Spain, during the first wave of COVID-19 infection and lockdown period when preventive measures were taken to avoid transmission among residents. Methods. Nine hundred forty-two residents and 846 staff members from nine nursing homes participated in the study (April 18 to June 20, 2020). All participants were tested for SARS-CoV-2 in the nasopharynx by PCR and for IgG antibodies detection. Microbiological status at sampling was define… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
2
2
0
Order By: Relevance
“…In all these environments, technologies helped bridge distances and isolation, allowing contact with health professionals, caregivers, and teachers to be maintained. The results reported in the study coincide in highlighting the importance of technologies [ 47 , 48 , 49 , 50 ].…”
Section: Discussionsupporting
confidence: 79%
“…In all these environments, technologies helped bridge distances and isolation, allowing contact with health professionals, caregivers, and teachers to be maintained. The results reported in the study coincide in highlighting the importance of technologies [ 47 , 48 , 49 , 50 ].…”
Section: Discussionsupporting
confidence: 79%
“…Moreover, residents (including patients and older adults) comprised the majority of patients with confirmed cases, suggesting an elevated risk due to their living arrangements and potentially compromised immunity. This observation is consistent with that of a Spanish study that reported a higher infection rate among nursing home residents than among staff [ 20 ]. In terms of case severity, our findings indicate that baseline conditions in both healthcare and non-healthcare settings could potentially influence patient outcomes [ 21 ].…”
Section: Discussionsupporting
confidence: 93%
“…The scientific literature reviewed has highlighted the high incidence of the disease and associated mortality in the older adult population in the early stages of the disease, with residents in nursing homes being the most highly affected [ 36 , 74 , 75 ], as has occurred in Spain [ 76 , 77 , 78 ]. This population group, due to its own socio-demographic conditions and age-associated chronic comorbidity and functioning, was the most vulnerable to SARS-CoV-2 infection, hospitalization, and death [ 61 , 79 , 80 , 81 ], with women being the group most affected by mortality [ 82 ].…”
Section: Discussionmentioning
confidence: 99%